Polymorphisms in the insulin-like growth factor axis are associated with gastrointestinal cancer. - Jennie Ong; Jody Salomon; Rene H M te Morsche; Hennie M J Roelofs; Ben J M Witteman; Polat Dura; Martin Lacko; Wilbert H M Peters (PLoS ONE, 2014)
INTRODUCTION: Numerous factors influence the development of gastrointestinal (GI) cancer. The insulin-like growth factor (IGF) axis plays a role in embryonic and postnatal growth and tissue repair. Elevated levels of IGFs, low levels of IGF binding proteins (IGFBPs) and over-expression of IGF receptor (IGFR-I) were associated with several stages of cancer. Here, the prevalence of the single nucleotide polymorphisms (SNPs) rs6214 in the IGF type I (IGF-I) gene and rs6898743 in the growth hormone receptor (GHR) gene in patients with GI cancer and controls was studied. MATERIALS & METHODS: In this Dutch case-control study, DNA isolated from blood of 1,457 GI cancer patients; 438 patients with head and neck cancer (HNC), 475 with esophageal cancer (EC) and 544 with colorectal cancer (CRC) and 1,457 matched controls, was used to determine the rs6214 and rs6898743 genotypes by polymerase chain reaction. The association between these SNPs and GI cancer, HNC, esophageal adenocarcinoma (EAC), esophageal squamous-cell carcinoma (ESCC) and proximal or distal CRC was studied. Odds ratios (ORs) with 95% confidence interval (95% CI) were calculated via unconditional logistic regression. RESULTS: Overall for GI cancer, the ORs for SNPs rs6214 and rs6898743 were approximately 1.0 (p-value>0.05), using the most common genotypes GG as reference. An OR of 1.54 (95% CI, 1.05-2.27) was found for EC for genotype AA of rs6214. The ORs for EAC were 1.45 (95% CI, 1.04-2.01) and 1.71 (95% CI, 1.10-2.68), for genotypes GA and AA, respectively. Genotype GC of rs6898743 showed an OR of 0.47 (95% CI, 0.26-0.86) for ESCC. CONCLUSION: The A allele of SNP rs6214 in the IGF-I gene was associated with EAC, and with HNC in women. The GC genotype of rs6898743 in the GHR gene was negatively associated with ESCC.